Changes in the strength of the polymer concrete used in the electroplating vats under operational load = Zmiany wytrzymałości betonu polimerowego stosowanego w wannach elektrolitycznych pod obciążeniem technologicznym - Radna, Lidia; Sakharov, Volodymyr (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Due to the strong and aggressive electrolyte media and thermal load, design of the electroplating vats in the copper industry often relies on the resin concrete. The article presents the results of the strength tests of the polymer concrete based on the "Derkane" resin, used in the construction of electroplating vats.
Keywords: polymer concrete; electroplating bath; laboratory test; compressive; bending tensile strength; hardening; polimerobeton; wanna elektrolityczna; badania laboratoryjne; ściskanie; zginanie; wytrzymałość na rozciąganie; hartowanie